1. Emotional Development through Art Expressions - Rusu Marinela (Sciendo, 2017)
Aesthetic education forms and develops a mental quality of the individual, namely, general receptivity to the world and life. It can be said, however, that aesthetic education includes a multiplicity of meanings, formative and educative in relation to personality. All this has a profound echo in the whole personality, whether at the emotional or behavioral level. Art touches and contributes to creating prints from which the later emotional pleasure, taste, artistic judgment and discernment on human values will develop. Emotion refers not only to the aesthetics but involves more often, ethics, behavioral preferences in choosing one or another conduct. Emotions enrich the register of artistic self-expression and complements the temperamental and the character profile of a person. Here we analyze these relevant issues in an experiment conducted at the "Elena Cuza" Primary School of Iasi, Romania. We also present the conclusions of Art Intervention in school for these students. Art intervention in school can become an affective-emotional aim in educator-student relationship and may have important, long term evolutionary consequences, referring to the achievement of personal ideals and efficiency of educational activity.